DIAGNOSIS OF CALCULATION DIFFICULTIES AT ELEMENTARY SCHOOL IN LOW CLASS - Herti Prastitasari; Cholis S Sa’dijah; Styo Mahendra Wasita Aji (E-CHIEF Journal, 2021)
The purpose of this study was to diagnose the difficulty of counting, the factor causing the difficulty of counting and the solution to the problem of learning difficulties in numeracy experienced by the lower grade students. This study uses a qualitative approach. This research data collection uses test, observation and interview. The data collected were analyzed with the stages of data reduction, data presentation and conclusions. Based on the result of the analysis of the data obtained, the result showed that subjects with high abilities did not have difficulty in counting. Subjects who are capable are having difficulty understanding concepts, difficulty distinguishing operating symbols, difficulty applying counting principles and difficulty translating questions. Subjects with low abilities have difficulty counting and distinguishing operating symbols, difficulty translating questions, and difficulty applying arithmetic principles. Factors causing difficulty in counting are the lack of motivation and interest of students in learning and students are not yet fluent in reading. The solution in overcoming these problems is to instil the concept of addition and subtraction of numbers to children using concrete and semi-concrete objects, the questions presented are using picture questions, both routine questions and story questions, and the use of media and learning models to generate interest and motivation in children in counting addition and counting subtraction.Keywords: learning difficulties, arithmetic operations, addition and subtraction